2010
DOI: 10.1161/strokeaha.109.571000
|View full text |Cite
|
Sign up to set email alerts
|

Neovascular Age-Related Macular Degeneration and the Risk of Stroke

Abstract: Background and Purpose-Using a nationwide population-based data set from Taiwan, this study investigated the relationship between neovascular age-related macular degeneration (AMD) and the risk of stroke over a 5-year period. Method-The study cohort comprised 209 patients who received treatment for AMD between 1999 and 2001. We randomly selected 1045 subjects matched with the study cohort in terms of age and gender for comparison. Cox proportional hazard regressions were performed to compare the 5-year stroke-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 27 publications
0
46
0
1
Order By: Relevance
“…9 The Blue Mountains Eye Study found that early and late AMD were not associated with stroke mortality, 10 whereas a study from Taiwan found that neovascular AMD increased the risk of stroke-related death. 7 Only 1 study divided stroke into subtypes and found that the risks of both cerebral infarction and intracerebral hemorrhage were increased in people with either neovascular or nonneovascular AMD. 8 However, a limitation of the study was that the classification of stroke and AMD were both based on medical reimbursement claims and therefore vulnerable to misclassification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The Blue Mountains Eye Study found that early and late AMD were not associated with stroke mortality, 10 whereas a study from Taiwan found that neovascular AMD increased the risk of stroke-related death. 7 Only 1 study divided stroke into subtypes and found that the risks of both cerebral infarction and intracerebral hemorrhage were increased in people with either neovascular or nonneovascular AMD. 8 However, a limitation of the study was that the classification of stroke and AMD were both based on medical reimbursement claims and therefore vulnerable to misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies that investigated the association between AMD and stroke reported inconsistent results. [7][8][9][10][11] Most studies did not distinguish between early and late AMD nor did they subdivide late AMD into dry (atrophic) or wet (neovascular) AMD. Besides, except for a study based on medical reimbursement claims, no previous study presented separate associations for the subtypes cerebral infarction and intracerebral hemorrhage.…”
mentioning
confidence: 99%
“…6 In the current issue of Stroke, Hu and colleagues further report on this association. 8 Using a national linkage database in Taiwan, the authors showed that patients with a neovascular AMD diagnosis had a 2-fold higher incidence of stroke than those without AMD (18.2% versus 9.9%), and this association persisted while controlling for concomitant vascular risk factors. One of the strengths of this study is the ability to study neovascular AMD cases; in population-based studies like the ARIC cohort, there were few late neovascular AMDs.…”
mentioning
confidence: 99%
“…In 15,771 new-onset neovascular AMD patients aged ≥65 years matched with 46,408 controls, Alexander et al [35] found similar rates of myocardial infarction and ischemic cerebral vascular accidents among neovascular AMD patients and controls. More recently, Hu et al [36] found in 209 neovascular AMD patients from Taiwan and 1,045 matched controls during a 5-year follow-up period a hazard ratio for stroke 2.01 times greater for patients with AMD than for patients without AMD. However, no significant difference was found between patients with AMD <65 years of age and age-matched controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hu et al [36] found in 209 neovascular AMD patients from Taiwan and 1,045 matched controls during a 5-year follow-up period a hazard ratio for stroke 2.01 times greater for patients with AMD than for patients without AMD. However, no significant difference was found between patients with AMD <65 years of age and age-matched controls [36]. As can be easily inferred from the above results, an association between neovascular AMD and stroke, myocardial infarction or cardiovascular disease is likely, but this link needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%